2022
DOI: 10.3390/foods11182859
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pinhole Plasma Jet Activated Water against Escherichia coli, Colletotrichum gloeosporioides, and Decontamination of Pesticide Residues on Chili (Capsicum annuum L.)

Abstract: Plasma activated water (PAW) generated from pinhole plasma jet using gas mixtures of argon (Ar) and 2% oxygen (O2) was evaluated for pesticide degradation and microorganism decontamination (i.e., Escherichia coli and Colletotrichum gloeosporioides) in chili (Capsicum annuum L.). A flow rate of 10 L/min produced the highest concentration of hydrogen peroxide (H2O2) at 369 mg/L. Results showed that PAW treatment for 30 min and 60 min effectively degrades carbendazim and chlorpyrifos by about 57% and 54% in solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Furthermore, the simultaneous reduction of bacterial load and elimination of fungal spores could be proven. 9,10 The incorporation of PAW in the food supply chain could thereby reduce pesticide residues, while simultaneously decreasing the risk of forming resistance. 9 In comparison to soil, wastewater is similarly affected by sanitisers, pesticides and fertiliser residues.…”
Section: Paw and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the simultaneous reduction of bacterial load and elimination of fungal spores could be proven. 9,10 The incorporation of PAW in the food supply chain could thereby reduce pesticide residues, while simultaneously decreasing the risk of forming resistance. 9 In comparison to soil, wastewater is similarly affected by sanitisers, pesticides and fertiliser residues.…”
Section: Paw and Healthmentioning
confidence: 99%
“…9,10 The incorporation of PAW in the food supply chain could thereby reduce pesticide residues, while simultaneously decreasing the risk of forming resistance. 9 In comparison to soil, wastewater is similarly affected by sanitisers, pesticides and fertiliser residues. Therefore, efficient wastewater treatment is needed to accomplish the vision of One Health.…”
Section: Paw and Healthmentioning
confidence: 99%
“…The application of PAW against Escherichia coli, Colletotrichum gloeosporioides, and the decontamination of pesticide residues on chili (Capsicum annuum L.) was investigated in [135]. The results showed that treatment for 30 min and 60 min effectively degraded carbendazim and chlorpyrifos.…”
Section: Atmospheric Pressure Plasma Jets and Plasma Torchmentioning
confidence: 99%
“…The analyses of the efficiency of pesticide degradation in grapes and strawberries using PAW showed chlorpyrifos degradation rates of 79% and 69% for grapes and strawberries, respectively, whereas the carbaryl degradation rates were 86% and 73%. Sawangrat et al [192] adopted a pinhole plasma jet to generate PAW; the carbendazim and chlorpyrifos contained in the solution and on the chili surface was subsequently degraded. For the same plasma configuration, they reported that the pesticide degradation efficiency was higher on the chili surface than in the pesticide solution.…”
Section: Degradation Of Pesticide Residues In Foodmentioning
confidence: 99%